Long‐term overall survival and toxicities of ABVD vs BEACOPP in advanced Hodgkin lymphoma: A pooled analysis of four randomized trials. (25th July 2020) - André, Marc P. E.; Carde, Patrice; Viviani, Simonetta; Bellei, Monica; Fortpied, Catherine; Hutchings, Martin; Gianni, Alessandro M.; Brice, Pauline; Casasnovas, Olivier; Gobbi, Paolo G.; Zinzani, Pier Luigi; Dupuis, Jehan; et al.
Abstract: Purpose: We explored the potential overall survival (OS) benefit of bleomycin, etoposide, doxorubicin (Adriamycin), cyclophosphamide, vincristine (Oncovin), procarbazine, and prednisone (BEACOPP) over doxorubicin (Adriamycin), bleomycin, vinblastine, and dacarbazine (ABVD) in a pooled analysis of four randomized trials. Patients and methods: Primary objective was to evaluate the OS impact of BEACOPP using individual patient data. Secondary objectives were progression‐free survival (PFS), secondary cancers, and use of autologous stem cell transplantation (ASCT). Results: About 1227 patients were included. The 7‐year OS was 84.3% (95% CI 80.8‐87.2) for ABVD vs 87.7% (95% CI 84.5‐90.2) for BEACOPP. Two follow‐up periods were identified based on survival curves and hazard ratio (HR) over time. For the first 18 months, there was no difference. For the second period of ≥18 months, ABVD patients had a higher death risk (HRABVD vs BEACOPP = 1.59; 95% CI 1.09‐2.33). A Cox model stratified by trial and evaluating the effect of treatment and International Prognostic Index (IPI) score as fixed effects showed that both were statistically significant (treatment, P = .0185; IPI score, P = .0107). The 7‐year PFS was 71.1% (95% CI 67.1‐74.6) for ABVD vs 81.1% (95% CI 77.5‐84.2) for BEACOPP ( P < .001). After ABVD, 25 secondary cancers (4.0%) were reported with no myelodysplasia (MDS)/acute myeloid leukemia (AML) compared to 36 (6.5%) after BEACOPP, which included 13 patients with MDS/AML. Following ABVD, 86 patients (13.8%) received ASCT vs 39 (6.4%) for BEACOPP. Conclusions: This analysis showed a slight improvement in OS for BEACOPP and confirmed a PFS benefit. Frontline use of BEACOPP instead of ABVD increased secondary leukemia incidence but halved the requirement for ASCT. Abstract : Advanced Hodgkin lymphoma (HL) are treated with two different chemotherapy regimens (doxorubicin [Adriamycin], bleomycin, vinblastine, and dacarbazine [ABVD] or bleomycin, etoposide, doxorubicin [Adriamycin], cyclophosphamide, vincristine [Oncovin], procarbazine, and prednisone [BEACOPP]) that have two different toxicity profiles. In this pooled analysis of four randomized trials comparing these two regimens, and with a median follow‐up of 7 years, progression‐free survival is significantly superior with the BEACOPP regimen. The 7 years overall survival was 84.3% for ABVD and 87.7% for BEACOPP. The main cause of death after ABVD is HL, but second malignancy including 10 myeloid malignancies after BEACOPP.